2013
DOI: 10.1177/0886260513504644
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Family Violence and Attachment Styles as Predictors of Dating Violence Perpetration Among Men and Women

Abstract: This study examined a multiple mediator model explaining how sibling perpetration and one's attachment style mediate the relation between parent-to-child victimization and dating violence perpetration. A sample of undergraduate students (n = 392 women, n = 89 men) completed measures of the aforementioned variables on an Internet survey. For men, path analyses found no mediation; parent-to-child victimization had a direct association with dating violence perpetration, no association was found between sibling pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 40 publications
(82 reference statements)
7
42
0
2
Order By: Relevance
“…Adolescents who reported more attachment anxiety were more likely to report more experiences of TDV perpetration 10 months later [ 40 ]. In a study of undergraduate students between the ages of 18 and 25, attachment anxiety and attachment avoidance were not significant predictors of dating violence perpetration in men; however, in women, attachment anxiety, and not attachment avoidance, was predictive of dating violence perpetration [ 41 ]. In a third study in a predominately African American sample it was found that for those with a secure attachment pattern, their history of childhood maltreatment was not a significant risk factor of dating violence [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who reported more attachment anxiety were more likely to report more experiences of TDV perpetration 10 months later [ 40 ]. In a study of undergraduate students between the ages of 18 and 25, attachment anxiety and attachment avoidance were not significant predictors of dating violence perpetration in men; however, in women, attachment anxiety, and not attachment avoidance, was predictive of dating violence perpetration [ 41 ]. In a third study in a predominately African American sample it was found that for those with a secure attachment pattern, their history of childhood maltreatment was not a significant risk factor of dating violence [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to family aggression was associated with perpetration of abuse among females with high avoidant attachment, while no association was found among those with low avoidance (Grych & Kinsfogel, 2010). Another study indicated that attachment anxiety mediated the association between parental maltreatment and dating perpetration for female university students (Lee, Reese-Weber, & Kahn, 2014). Since prior associations between childhood maltreatment and insecure attachment styles in late adolescence and adulthood have been noted in prior studies (Finzi et al, 2001; Gauthier, Stollak, Messé, & Aronoff, 1996), and there is some limited research indicating attachment insecurity may moderate the association between childhood abuse and adolescent dating violence, this study aimed to explore associations among childhood maltreatment, attachment styles, and dating violence perpetration and victimization in a high risk, community sample of late teens, and to identify the moderating role attachment style may play on the association of childhood maltreatment and later adolescent dating violence perpetration and victimization.…”
Section: Introductionmentioning
confidence: 99%
“…College-age individuals and, in particular, students in the early years of college are at higher risk due to their absence from parents and their established support systems, as well as their younger age and normative use of alcohol. Furthermore, bidirectional violence is the most common pattern in college dating relationships (Lee, Reese-Weber, & Kahn, 2014), suggesting that men and women perpetrate and experience IPV (Kaukinen, Gover, & Hartman, 2012), leading to more frequent and intense conflicts between couples.…”
mentioning
confidence: 99%